Images of Crisis and Opportunity. A Study of African Migration to Greece - Veikou, Mariangela (Qualitative Sociology Review, 2013)
The economic crisis in Greece is becoming a way of life and it is affecting, among other things, the way the Greek society views immigration. Greek people are waking up to the reality that immigrants in the streets of big cities would not go back. The kind of economic state of emergency in need of all sorts of austerity measures the Greek society is entering, shockingly, brings about the fear even in liberal minds that the country cannot provide for all. In this paper I draw from my own newly conducted ethnographic study to explore two interconnected themes: the study of local aspects of integration of Sub-Saharan African migrants in the city center of Athens, Greece and the use of photographic images in ethnographic research. More specifically, the paper discusses the representations of difference via a series of contemporary street photographs depicting everyday life instances of African migrants in the city center of Athens. It thus creates a visual narrative of metropolitan life, which forms the basis for a discussion on three themes related to discourses on migrant integration in light of today’s economic crisis: a) the physical and social environment of marginalization, b) the migrant body, and c) the fear of the migrant.